Evaluation of Sequential Oral Versus Intravenous Antibiotic Treatment of Enterococcus faecalis Bloodstream Infections - Loudermilk, Carly; Eudy, Joshua; Albrecht, Stephanie; Slaton, Cara N; Stramel, Stefanie; Tu, Patrick; Albrecht, Benjamin; Green, Sarah B; Bouchard, Jeannette L; Orvin, Alison I; Caveness, Christian F; Newsome, Andrea Sikora; et al. (The Annals of pharmacotherapy, 2025)
Intravenous (IV) antibiotics have historically been considered standard of care for treatment of bloodstream infections (BSIs). Recent literature has shown sequential oral (PO) therapy to be noninferior to IV antibiotics for certain pathogens and disease states. However, a gap exists in the literature for BSI caused by . To compare outcomes of definitive sequential PO therapy to definitive IV therapy in patients with BSI. Multicenter, retrospective, matched cohort study of adult patients with at least one blood culture positive for from January 2017 to November 2022. Patients with polymicrobial BSI, concomitant infections requiring prolonged IV antibiotic therapy, those who did not receive antibiotic therapy, and those who died within 72 hours of index culture were excluded. Subjects were matched based on source of infection in a 2:1 (IV:PO) ratio. The primary outcome was a composite of all-cause mortality and treatment failure. Secondary outcomes included hospital length of stay (LOS), antibiotic duration, and 30-day readmission rate. Of the 186 patients who met criteria for inclusion, there was no statistically significant difference in the primary composite outcome for PO compared to IV therapy (14.5% vs 21.8%; OR 0.53 [0.23-1.25]) or 30-day readmission (17.5% vs 29%; OR 0.53 [0.25-1.13]). Hospital LOS was significantly longer in patients receiving IV-only therapy (6 days vs 14 days; < 0.001). Sequential oral therapy for BSI had similar outcomes compared to IV-only treatment and may be considered in eligible patients.